POTENTIALS OF ELECTRONIC BUSINESS DEVELOPMENT IN SERBIA - Milovanović, Slavoljub (Economics of Agriculture, 2016)
Intensive application of information and communication technology (ICT), particularly Internet in selling and buying business processes have caused development of electronic business (e-business) concept. Numerous organizations in the world and in Serbia as well have implemented the concept. The basic aim of the paper is to analyse level of internet technology and e-business implementation in Serbia. The paper has theoretical background explaining concept of e-business and ICT which supports the implementation of this concept. However, empirical or practical contribution of the paper is articulated through analysis of data considering application of ICT and e-business concept in Serbia. The data considering application of ICT and e-business concept in Serbia is collected by Statistical Offce of the Republic of Serbia and encompasses households/individuals and enterprises in Serbia. Results of the research presented in the paper can help executives in Serbian organizations in planning e-business concept implementation as well as researchers in deeper study of this theme.